Changes in pneumococcal vaccine coverage in the Canadian Longitudinal Study on Aging (CLSA): An analysis based on the 2018–2021 follow-up 2 survey - Giorgia Sulis; Nawal Maredia; Christina Wolfson; Nicole E. Basta (PLoS ONE, 2026)
Introduction Pneumococcal vaccination is recommended for older adults and individuals with chronic medical conditions (CMC) due to the high risk of invasive pneumococcal disease in these groups. Despite this, vaccination coverage in Canada remains below the national target of 80%, to be achieved by 2025. We conducted a new analysis of recently released data from the Canadian Longitudinal Study on Aging (CLSA), aimed at providing estimates of pneumococcal vaccine coverage from 2018–2021 among eligible adults, identifying sociodemographic disparities, and exploring changes over time since 2015. Methods The CLSA, a nationally representative cohort launched in 2011, recently released data collected during the second follow-up visit (FUP2; 2018–2021). We conducted a cross-sectional analysis of participant self-reported pneumococcal vaccination status, stratified by sociodemographic characteristics, receipt of influenza vaccine in the previous 12 months, and contact with family doctor in the previous 12 months. Logistic regression was used to identify factors associated with being newly vaccinated for pneumococcal disease as reported during FUP2 compared with three years earlier during follow-up 1 (FUP1; 2015–2018). We previously reported pneumococcal vaccination estimates for 2015–2018. Results Only 56.8% (95% CI: 55.8–57.7%; n = 10,530) of eligible study participants aged 65 years and older and 19.3% (95% CI: 18.1–20.5%; n = 4,055) of those aged <65 years with at least 1 chronic medical condition reported having received the pneumococcal vaccine when surveyed between 2018–2021. Males, rural residents, and individuals in certain provinces reported lower vaccination rates. Compared to three years prior, 28.4% of participants aged 65 years and older and 11% of participants aged <65 years with at least one CMC reported being newly vaccinated. Higher odds of being newly vaccinated were observed among individuals who reported having received influenza vaccination in the previous 12 months in both age groups. Conclusions Pneumococcal vaccine coverage among Canadian adults aged 65 and older enrolled in the CLSA increased by only 2% between 2015–2018 and 2018–2021, and no changes were observed among those under the age of 65 with underlying conditions.